2020
DOI: 10.1002/hpja.404
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a scale to assess Australian children’s perceptions of their swimming competence and factors associated with child and parent perception

Abstract: Issue Addressed: Drowning is a global public health issue. Aims were to assess: (a) face validity of the "Pictorial Scale of Perceived Water Competence (PSPWC)," (b) the association between child and parent perception of child swimming competence and (c) factors associated with perception of child swimming competence. Methods: Child-parent dyads and swim instructors were recruited for a mixed method study. Children aged 4-8 years (n = 51) reported on: familiarity, progressions and their own swim competence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…(2016) indicated that both children and parents found it harder to accurately estimate a child’s aquatic skill level when the child was less skilled. In contrast, also using the PSPWC, De Pasquale et al. (2020) found no association between 4-8 year-old children’s and their parent’s perceptions of their swimming ability and reported that swimming level (i.e., beginner, intermediate or squad category, based on a standardized ranking system created by the researchers) was positively associated with children’s self-perception but not with the parent’s perceptions.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…(2016) indicated that both children and parents found it harder to accurately estimate a child’s aquatic skill level when the child was less skilled. In contrast, also using the PSPWC, De Pasquale et al. (2020) found no association between 4-8 year-old children’s and their parent’s perceptions of their swimming ability and reported that swimming level (i.e., beginner, intermediate or squad category, based on a standardized ranking system created by the researchers) was positively associated with children’s self-perception but not with the parent’s perceptions.…”
Section: Discussionmentioning
confidence: 84%
“…(2020) found no association between 4-8 year-old children’s and their parent’s perceptions of their swimming ability and reported that swimming level (i.e., beginner, intermediate or squad category, based on a standardized ranking system created by the researchers) was positively associated with children’s self-perception but not with the parent’s perceptions. De Pasquale et al. (2020) concluded that children have a better understanding of their swim competence than their parents do, suggesting parent education is needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations